Teaching and Learning of Piano Timbre Through Teacher–Student Interactions in Lessons - Li, Shen; Timmers, Renee (Frontiers in Psychology, 2021)
The ability to play with a variety of timbres on the piano relates to advanced pianistic skills for a performer; however, little is known regarding how the skills are acquired in piano lessons. The literature review draws attention to the sound-producing/facilitating gestures, bodily awareness, and proprioceptive feelings in piano playing, suggesting the adoption of a “mind-body integration” perspective to investigate the teaching and learning of piano timbre in lessons. An observational study was conducted among three pairs of university-level teachers and students, to understand the teaching/learning process of piano timbre and teacher-student interaction in the context of higher music education. The results suggested that piano timbre is not learnt through imitation or as a ‘fixed’ and objective knowledge, but as a co-constructed conception between the teachers and the students. The meaning of timbre goals in piano lessons is enacted through ‘in-the-moment’ bodily experience and embodied through performance actions. This study sheds lights to rethink the ‘master-apprentice’ model in the learning o musical instrumental and to understand the teacher’s role in helping with student’s mind-body integration in the tone production.